Rainbow smelt Osmerus mordax dentex in the shelf zone and inland water bodies of Kamchatka: state of stock, fishery, and biological structure - Alexander V. Bugaev; Yury N. Amelchenko; Sergey V. Lipnyagov (Известия ТИНРО)
Stock and biological structure of rainbow smelt Osmerus mordax dentex in the water bodies of Kamchatka are considered. In total, 14,156 individuals are analyzed in 2005-2013; age is determined for 11,954 of them. The stock is assessed by bottom trawl and Danish seine surveys in the shelf zone of Kamchatka (13 surveys in 2005-2013). State of the stock is evaluated as good, in general, but some unbalance between its northern and southern parts is noted in recent years: the former one grows and its state is very good recently but the latter one has a tendency to decrease though its state is still satisfactory. Dynamics of the major biological parameters of smelt, as sex ratio, body size and weight, and age structure, indicate also some features of its southern sub-stock degradation, as size and weight decreasing and lowering the age in catches. In particular, these changes are clear in the Petropavlovsk-Commander fishery district, where they are presumably caused by large-scale unregulated sport and amateur fisheries with the summary annual landing about 1-2 thousand tons of rainbow smelt that is comparable with its commercial withdrawal. These activities affect mostly on immature fish that destruct the whole stock of rainbow smelt.